Analisis Konten pada Media Sosial Instagram @Kemndiktisaintek.ri sebagai Penyebaran Informasi & Komunikasi - Sigit Budiono; Ahmad Toni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Content analysis on the Instagram account of the Ministry of Higher Education, Science, and Technology of the Republic of Indonesia, through the account @kemndiktisaintek.ri, has become a relevant topic in the digital era as a means of disseminating information and public communication. Instagram is a social media platform with wide reach and interactive features that government agencies can utilize to build effective communication with the public. Various studies have shown that Instagram can be an effective medium for conveying information if supported by good information quality, such as completeness, relevance, accuracy, timeliness, and attractive content presentation. Digital communication strategies on Instagram also require careful content planning and optimal utilization of platform features to create two-way interactions with the audience. However, several studies have found that government agency social media accounts still face challenges in increasing content interactivity and appeal, resulting in less than optimal public engagement. Therefore, creative, informative, and participatory content management is a crucial factor in increasing the effectiveness of public communication. In addition to being an information medium, Instagram can also function as a crisis communication tool that helps government agencies convey policies, clarify issues, and rebuild public trust. Therefore, optimizing Instagram content management strategies is a crucial step for government agencies in increasing the effectiveness of information dissemination and digital communication to the wider public.